Food waste recycling: Utilization, management, and innovation - Monsurat Bello; Cecilia A. Olarewaju; Folasade Esther Awosejo (International Journal of Academe and Industry Research)
This study assessed the nature of food waste and potential of food waste recycling in Ilesha West Local Government Area of Osun. Using descriptive research design aided by waste management hierarchy framework, this study gathered data using structured questionnaire distributed to a total sample size 210. The questionnaire was constructed and validated by the researcher’s supervisor and two other experts with Cronbach’s Alpha of 0.83, signifying reliability of the instrument's internal consistency. Data collected were analyzed using both descriptive and inferential statistics. Findings revealed that households, restaurants, and markets generate food waste in large quantities. This implies that large food waste types are generated from different food outlets and if not properly managed could cause environmental pollution, health risks, economic loss, food insecurity, climate change, resource waste, and greenhouse emissions. Innovative use of food waste can bring about improved waste management, economic benefits, environment conservation as well as food security. Theoretically, it can contribute to waste management theory, assessment of recycling technologies, and development of a sustainable food system and this study can form a framework for the development of policy and regulation that supports food waste recycling and reduction in Ilasha West Local Government of Osun state. It is recommended that educational campaigns and local community meetings be organized to educate households, markets, and restaurants about the risks associated with improper waste disposal and to emphasize the importance of adopting sustainable waste management practices.